What Purpose Do Corporations Purport? Evidence from Letters to Shareholders - Raghuram G. Rajan; Pietro Ramella; Luigi Zingales (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2022)
Using natural language processing, we identify and categorize the corporate goals in the shareholder letters of the 150 largest companies in the United States, from 1955 to 2020. Corporate goals have proliferated during this period from an average of two in 1955 to almost 10 in 2020. We find a variety of factors are associated with a corporation stating a specific goal including advertising a firm's strengths, promising improved performance, signaling a commitment to specific constituencies, building societal legitimacy, and conforming to the behavior of other corporations. In spite of the proliferation of corporate goals, executive compensation is still overwhelmingly based on shareholder value, as measured by stock prices and financial performance. Yet, we do observe a rise in bonus payments made contingent on social and environmental objectives, especially among the signatories of the 2019 Business Roundtable statement on corporate purpose.
Keywords: 330